Tetramethylpyrazine Improves Cognitive Impairment and Modifies the Hippocampal Proteome in Two Mouse Models of Alzheimer's Disease - Huang, Xianfeng; Yang, Jinyao; Huang, Xi; Zhang, Zaijun; Liu, Jianjun; Zou, Liangyu; Yang, Xifei (Frontiers in cell and developmental biology, 2021)
Alzheimer's disease (AD), one of the most common neurodegenerative diseases, has no effective treatment. We studied the potential effects of tetramethylpyrazine (TMP), an alkaloid in the rhizome of Ligusticum chuanxiong Hort. used in Traditional Chinese Medicine ( chuānxiong ) to treat ischemic stroke, on AD progression in two AD mouse models. Eight-month-old 3xTg-AD mice received TMP treatment (10 mg/kg/d) for 1 month, and 4-month-old APP/PS1-AD mice received TMP treatment (10 mg/kg/d) for 2 months. Behavioral tests, including step-down passive avoidance (SDA), new object recognition (NOR), Morris water maze (MWM), and Contextual fear conditioning test showed that TMP significantly improved the learning and memory of the two AD-transgenic mice. In addition, TMP reduced beta-amyloid (Aß) levels and tau phosphorylation (p-tau). Venny map pointed out that 116 proteins were commonly changed in 3xTg mice vs. wild type (WT) mice and TMP-treated mice vs. -untreated mice. The same 130 proteins were commonly changed in APP/PS1 mice vs. WT mice and TMP-treated mice vs. -untreated mice. The functions of the common proteins modified by TMP in the two models were mainly involved in mitochondrial, synaptic, cytoskeleton, ATP binding, and GTP binding. Mitochondrial omics analysis revealed 21 and 20 differentially expressed mitochondrial proteins modified by TMP in 3xTg-AD mice and APP/PS1 mice, respectively. These differential proteins were located in the mitochondrial inner membrane, mitochondrial outer membrane, mitochondrial gap, and mitochondrial matrix, and the function of some proteins is closely related to oxidative phosphorylation (OXPHOS). Western-blot analysis confirmed that TMP changed the expression of OXPHOS complex proteins (sdhb, ndufa10, uqcrfs1, cox5b, atp5a) in the hippocampus of the two AD mice. Taken together, we demonstrated that TMP treatment changed the hippocampal proteome, reduced AD pathology, and reduced cognitive impairment in the two AD models. The changes might be associated with modification of the mitochondrial protein profile by TMP. The results of the study suggest that TMP can improve the symptoms of AD.